Establishment of co-infection and hybridization of Haemonchus contortus and Haemonchus placei in sheep - Santos, M. C. [UNESP] (2018)
This study aimed to evaluate the simultaneous infections of Haemonchus contortus and Haemonchus placei in sheep, as well as the production of hybrids. A parental group of lambs (n = 6) were mix-infected with 2000 infective larvae (L3) of H. placei and 2000 L3 of H. contortus. Faecal samples were taken from each of these six lambs to produce the first generation of L3 (F1-L3) in individual cultures. These F1-L3 were used to infect 12 lambs; six of them were euthanized at 42 days (Group F1-42) and six at 84 days (Group F1-84) post infection. Polymerase chain reaction (PCR) analysis, using species-specific primer pairs, was the gold standard method for identification of Haemonchus adult species and hybrids. The establishment rate of both species was similar in the parental group: 51.7% H. contortus and 48.3% H. placei. Of the 219 adult specimens from groups F1-42 and F1-84 analysed by PCR, eight (3.65%) were hybrids, 111 were H. contortus and 100 were H. placei. The morphological evaluation of the F1-L3 from the parental group showed a predominance of larvae with H. contortus size (51.5%) in comparison with H. placei (42.8%). In the second generation of L3 (F2-L3) produced by the F1-lambs, larvae with H. contortus morphology predominated, with 81.5% in the F1-42 group and 84.0% in the F1-84 group. In conclusion, an artificial mixed infection by H. contortus and H. placei was established in lambs and resulted in the production of a small number of hybrids among their offspring.